Cerebrospinal fluid biomarkers of neurodegeneration in narcolepsy type 1. Issue 2 (25th September 2019) - Baiardi, Simone; Pizza, Fabio; Polischi, Barbara; Moresco, Monica; Abu-Rumeileh, Samir; Plazzi, Giuseppe; Parchi, Piero
Abstract: Study Objectives: To measure the levels of five neurodegenerative biomarkers in the cerebrospinal fluid (CSF) of patients with narcolepsy type 1 (NT1) with variable disease duration. Methods: Following a standardized protocol of CSF collection and storage, we measured CSF total- and phosphorylated-tau, amyloid-beta 1–40 and 1–42, and neurofilament light chain (NfL) proteins in 30 nonneurological controls and 36 subjects with NT1, including 14 patients with recent disease onset (i.e. ≤12 months, short disease duration group). Results: CSF levels of all biomarkers were similar in NT1 subjects and controls. The comparison between NT1 with short and long disease duration only revealed slightly higher levels of CSF amyloid-beta 1–40 in the former group (median 9, 549.5, interquartile range [IQR] 7, 064.2–11, 525.0 vs. 6, 870.0, IQR 5, 133.7–9, 951.2, p = 0.043). CSF storage time did not influence the levels of the tested biomarkers. Conclusions: The measurement of CSF total-tau, phosphorylated-tau, amyloid-beta 1–40 and 1–42, and NfL proteins is not informative in NT1.